The timing of growth faltering in India has changed significantly over 1992-2016, with variations in prenatal and postnatal improvement (P10-005-19) - Headey, Derek D.; Menon, Purnima; Nguyen, Phuong Hong (Oxford University Press, 2019)
India accounts for a third of the global population of stunted preschoolers. However, very few studies have documented the timing of growth faltering in India, its evolution over time, or its variation over India's diverse regions. This study develops an approach for estimating the speed of growth faltering and applies it to multiple rounds of national and state-level data.